Classical Cryptography of Winds Eye Cell Circles - Saputro, Razis Aji; Sokawati, Risti; Mudrikah, Mudrikah; Puspita, Nikken Prima (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2016)
This classic cryptographic algorithms was designed from the concept of cardinal directions and the S-box. circles Concept given 16 directions winds and 8 circles lined with each cells according to ASCII table. The process of encryption algorithm using two kinds of key symbol that are (k1) form 16 symbols of the wind, and (k2) is a 7-bit binary number. plaintext encryption process become chiperteks1 with forming angle against north wind and k1 roomates are from plaintext rotating accordance angle formed. Chipertext 1 to chipertext 2 using binary numbers divided become r1 as directions displacement away from the center circle and r2 move with rotating around the center circle. Spinning process followed directions clockwise circle if even if odd and vice versa. Decryption process is done by doing a backward on the algorithm by using the key k2 (r2 then r1) and then r1. Spins counter-encryption process. Â©2016 JNSMR UIN Walisongo. All rights reserved.